2014
DOI: 10.5114/wiitm.2014.41623
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of incisional and ventral hernias with the new type of meshes: randomized control trial.

Abstract: IntroductionLaparoscopic incisional and ventral hernia repair (LIVHR) was first reported by Le Blanc and Booth in 1993. Many studies are available in the literature that have shown that laparoscopic repair of incisional and ventral hernia is preferred over open repair because of lower recurrence rates (less than 10%), less wound morbidity, less pain, and early return to work.AimTo identify the long-term outcomes between the different types of meshes and two techniques of mesh fixation, i.e., tacks (method Doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…All studies used a minimum mesh overlap of 3–5 cm. Thirty studies reported the percentage of patients at last follow‐up, with a median of 98 (range 76–100) per cent. Follow‐up was given as either a mean or median value, with an overall median of 22 (range 6–64) months.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies used a minimum mesh overlap of 3–5 cm. Thirty studies reported the percentage of patients at last follow‐up, with a median of 98 (range 76–100) per cent. Follow‐up was given as either a mean or median value, with an overall median of 22 (range 6–64) months.…”
Section: Resultsmentioning
confidence: 99%
“…There was an unclear risk of attrition bias in three studies as they did not describe patients lost to follow‐up. The risk of funding bias was unclear in two studies that did not describe the source of funding, and high in five studies that were funded by industry. The remaining three studies reported no funding from industry and had a low risk of funding bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations